Conexões afetivas na Educação Infantil: uma revisão de literatura - Pesavento, Debora Stela (2022)
Affection in the relationship between teachers and students is an inseparable part of the teaching and learning process and constitutes a relevant topic of study. In Early Childhood Education, affectivity gains emphasis, because, in addition to teaching and learning formal concepts that precede reading to exercise and education, the teacher also performs basic care with the child, as well as teaching daily life skills. According to the studies carried out in this research, affection in the teacher-student relationship plays an indispensable role for the concrete learning. The general objective of this research is to verify the insertion of affection between teachers and students of Early Childhood Education, trying to answer the following question: how does the literature approach the problem of the relationship between affectivity and the teaching-learning process in Early Childhood Education? The research objectives are: (I) to understand childhood and the trajectory of Early Childhood Education in Brazil and its relations with affection, through bibliographic research, based on the theories of authors such as Ausubel and Wallon; (II) to quantify scientific works that approach the theme in the journals platforms of Capes, Scielo, Unicamp electronic scientific journals portal and UFMG electronic university library, in order to verify the relevance of this theme in the area of Education; (III) to analyze the perception of affection in the works selected as object of study through a literature review. Methodologically, this is a approach research qualitative, through bibliographic research that includes data quantification and literature review. The results point to a certain stigmatization of affection in teaching practices that, according to research, devalues the Early Childhood Education professional, as it supposedly mischaracterizes the pedagogical action. Thus, we identified, through analysis, affection as imperative and predominantly related to care practices, dissociating it from teaching practices.